Public opinion model based on super-influencer integrating network community and content - Jianliang WEI; Hao JI; Tengyan TIAN; Shengli ZHOU (Dianxin kexue)
Aiming at the abnormal deviation and distortion of online public opinion,a public opinion model based on super-influencer integrating network community and content was designed.Deffuant-Weisbuch (DW) model was adopted,and factors such as user relationship,node identity and information noise were incorporated into the model,and the generation of public opinion deviation was simulated through simulation experiments.The results indicate that super-influencer leads to irreversible deviation of network public opinion,controversial content causes opinion fluctuation and convergence,but not the final opinion as a whole.There are differences in the interference effect between strong and weak communities,and by increasing the internal strength and external influence of the community,it can conduct public opinion confrontation with super-influencer,thus reversing the direction of public opinion deviation.